Effectiveness of Handling Human Rights-Based Public Complaints - Marsellia, Dini; Situmeang, Ampuan; Disemadi, Hari Sutra (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: This research examines the effectiveness of handling human rights-based public complaints at the Regional Inspectorate of Riau Islands Province.Purposes of the Research: The aim is to evaluate the implementation, obstacles, and efforts to optimize complaint management.Methods of the Research: Method used is an empirical legal research method with a statutory and empirical approach. Data were obtained through interviews, observations, and study of legal documents related to the handling of public complaints.Results Main Findings of the Research: Results showed that although the regulatory framework exists, its implementation has not been optimal. The main obstacles include limited human resources both in number and competence, lack of socialization to the community, and weak legal structure and culture. This has led to slow processing of complaints and a low level of responsiveness to community needs. Recommendations include improving HR competencies through regular training, strengthening socialization to raise public awareness, and optimizing technology to support complaints management. These measures are expected to ensure respect for and fulfillment of human rights in public services, increase public trust in the government, and support clean and accountable governance.